Efektifitas Democracy Assistance USAID Bagi Pertumbuhan Ekonomi Timor Leste - Aryani, Maria Indira (Global and Policy Journal of International Relations, 2013)
ABSTRACTThis research will examine USAID’s democracy assistance for Timor Leste’s economic growth. The background of this research was Timor Leste’s failure as well as many challenges faced in order to create political stability after having received USAID’s democracy assistance. Hence, the research question from this background would be “why USAID’s democracy assistance provided through the Election and Processes framework has not been seen effective to bring positive impacts for Timor Leste’s economic growth?”. This question is analysed by using the foreign aid effectiveness framework, the assumption of democracy and economic growth connectivity and the assumption of political stability and economic growth connectivity. The conclusion of this analysis is that USAID’s democracy assistance provided to Timor Leste has not effectively support Timor Leste’s economic growth since there are some aid effectiveness characteristics that does not correspond with the characteristic and ability of the people Timor Leste. The disrepancy slows down the process of acceptance of democracy that led to the slow pace of individual understanding of the importance of political process. The slow process led to some cases of political conflict and violence in Timor Leste, disrupting political stability in Timor Leste, which ultimately risen the challenges to Timor Leste’s economic growth.Keywords: democracy assistance, foreign aid effectiveness, democracy, political stability, economic growth.DOI:https://doi.org/10.33005/jgp.v1i02.1994